Contact Characteristic Analysis of Double Circular Arc Helical Gearing - Zhu Linlin; Wu Baolin; Li Yang (Jixie chuandong)
The three- dimensional parametric modeling of double arc helical gearing is completed based on Pro / E software,and a finite element model is built in ANSYS Workbench 14. 5 with the degree of coincidence factors of double circular arc gear meshing transmission,the statics analysis are obtained in the case of a meshing cycle on the deformation. The relationship between tooth profile radius difference Δρ,helix angle β and gear contact stress is analyzed,it has certain reference value for the design and calculation of the double arc helical gearing.